A TOPCon battery main grid silver paste and preparation method thereof

By using a specific composition of main gate silver paste in TOPCon batteries, the problem of poor wetting of silver aluminum paste and welding tape is solved, and good welding adhesion and photoelectric conversion efficiency are achieved.

CN114283960BActive Publication Date: 2025-02-07ZHEJIANG GUANGDA ELECTRONICS TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111530341.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-15
Publication Date
2025-02-07
Estimated Expiration
2041-12-15

AI Technical Summary

Technical Problem

When the components of the TOPCon battery are soldered in a string, the wettability of the silver aluminum paste and the lead-tin soldering tape is extremely poor, resulting in poor welding and affecting the reliability of the components.

Method used

A kind of mixed silver powder including 78-85 wt% of the main glass powder, 1-5 wt% of the main glass powder Pb-Si-Ti-Zn oxide, 0.1-2 wt% of the auxiliary glass powder Bi-Si-Mn-Cu oxide, 8- The main gate silver paste of 20 wt% organic carrier and 0.5-5 wt% organic additives can improve the density and welding adhesion of the silver paste by adjusting the particle size of the silver powder and the composition of the glass powder.

Benefits of technology

The good wetting and welding adhesion between silver aluminum paste and welding tape is achieved, the problem of failure to weld and the reliability of the components and the photoelectric conversion efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to a main grid silver paste for a TOPCon battery, comprising: 78-85wt% of mixed silver powder, 1-5wt% of main glass powder Pb-Si-Ti-Zn oxide, 0.1-2wt% of auxiliary glass powder Bi-Si-Mn-Cu oxide, 8-20wt% of organic carrier, and 0.5-5wt% of organic additive; the mixed silver powder is a mixture of spherical silver powder A, quasi-spherical silver powder B and nano silver powder C; the main grid silver paste has a fineness of less than 8μm and a viscosity of 90-150Pa·S / 25°C at a rotation speed of 5rmp. The main grid silver paste has a wide sintering window and a high photoelectric conversion efficiency, and can simultaneously meet the use of the front and back main grid electrodes of the TOPCon battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of crystalline silicon solar cells, and in particular to a main grid silver paste applied to a TOPCon cell and a preparation method thereof. Background Art

[0002] According to the data on new energy installed capacity in 2020, by the end of 2020, the total installed capacity of electricity in China was about 2.2 billion kilowatts, and the total installed capacity of wind and solar power exceeded 530 million kilowatts, accounting for 24%. The 2030 carbon peak target is that the total installed capacity of wind and solar power should reach 1.2 billion kilowatts, which means doubling within 10 years. The 530 million kilowatts of wind and solar power generation capacity was completed in about 15 years. Although the current production capacity, technology, and industrial chain are more mature and complete, the difficulty of achieving it still exists.

[0003] It is particularly important to improve the conversion efficiency of crystalline silicon solar cells. After nearly five years of development, the conversion efficiency of PERC cell technology has approached its limit. The new generation of TOPCon cell technology is becoming more and more mature. Since most of the silver paste on the front of TOPCon cells uses silver-aluminum paste (the addition of aluminum is indispensable), the wettability of aluminum and lead-tin solder strips is extremely poor during component string soldering, and even soldering cannot be performed, which greatly reduces the reliability of the components in long-term use.

[0004] In order to solve this technical problem, the DUP (step-by-step printing) printing technology is adopted to use the main grid electrode paste, that is, the silver-aluminum paste only prints the fine grid, and the welding electrode prints the main grid paste. The function of the fine grid is mainly to collect the photoelectron flow generated by the light on the surface of the battery. It needs to have excellent ohmic contact with the silicon substrate of the battery. The main function of the main grid is to collect the current of the fine grid line and provide welding adhesion when the components are serially welded. The main grid paste needs to have excellent welding bonding strength and no ohmic contact with the welding strip of the component serial welding. At the same time, the main grid paste needs to have good wettability with the silver-aluminum paste.

[0005] On the one hand, through material design, the main grid paste only combines with the passivation layer substrate material (silicon nitride substrate) on the surface of the battery after sintering, providing excellent mechanical bonding force. However, it does not produce metalized ohmic contact with the PN junction substrate material that constitutes the silicon battery, which can effectively reduce the metal complex on the battery surface and improve the photoelectric conversion efficiency of the battery.

[0006] On the other hand, a low-silver-content main grid electrode paste is used to replace the traditional high-silver-content front silver-aluminum paste as the main grid of the front electrode of the battery cell, thereby reducing the use of high-silver-content front silver-aluminum paste, thereby reducing manufacturing costs.

[0007] The most important point is that the main grid paste can effectively solve the problem that silver-aluminum paste is difficult to weld after sintering, while ensuring the aging adhesion requirements during the use of components, and can simultaneously meet the use of the front and back main grid electrodes of crystalline silicon solar TOPCon cells.

[0008] The present invention provides a main grid silver paste for TOPCon cells and a preparation method thereof, which solves the technical problem of using DUP technology to overcome the difficulty in welding the single printing of silver-aluminum paste for TOPCon and the Pb-Sn welding strip during component string welding. Summary of the invention

[0009] In order to solve the above technical problems and overcome the shortcomings of the prior art, the purpose of the present invention is to provide a main grid silver paste applied to TOPCon batteries, and the technical point is: the main grid silver paste applied to TOPCon batteries includes: 78-85wt% mixed silver powder, 1-5wt% main glass powder Pb-Si-Ti-Zn oxide, 0.1-2wt% auxiliary glass powder Bi-Si-Mn-Cu oxide, 8-20wt% organic carrier, and 0.5-5wt% organic additive;

[0010] The mixed silver powder is a mixture of spherical silver powder A, quasi-spherical silver powder B and nano silver powder C. In the mixed silver powder: the content of spherical silver powder A is 1-95wt%, the content of quasi-spherical silver powder B is 1-95wt%, and the content of nano silver powder C is 0-10wt%, preferably 2-6wt%.

[0011] The median particle size of the spherical silver powder A is 1.1-1.4 μm, and the tap density is 5-6 g / cm 3 The median particle size of the spherical silver powder B is 1.5-2.0 μm, and the tap density is 5.5-6.5 g / cm 3 The median particle size of the nano silver powder C is 0.5-0.8 μm, and the tap density is 4.5-5.5 g / cm3; the sintered density of the mixed silver powder is 6.5-9.5 g / cm 3 ;

[0012] The benefits of mixed silver powder include: the median particle size shows a gradient change. By adjusting the proportion of silver powders with different median particle sizes, the silver powder can be made denser after sintering, reducing the series resistance of the battery and improving the battery's fill factor.

[0013] The main glass powder includes the following components calculated in molar percentage: PbO 8-28mol%, SiO2 25-50mol%, TiO2 5-25mol%, ZnO 4-16mol% and X1-10mol%, wherein X includes any one or a combination of two or more of TeO2, Bi2O3, B2O3, MgO, CaO, BaO, Cr2O3, MoO3 and WO3.

[0014] The auxiliary glass powder includes the following components calculated in molar percentage: Bi2O3 5-24mol%, SiO2 30-55mol%, CuO 5-25mol%, MnO2 1-15mol% and Y 1-10mol%, wherein Y includes any one or a combination of two or more of TeO2, ZnO, B2O3, MgO, CaO, BaO, Cr2O3, MoO3 and WO3.

[0015] The particle size D50 of the two glass powders is between 0.5 and 4 μm.

[0016] The main glass powder is a Pb-Si-Ti-Zn oxide system, which has the characteristics of weak corrosion to SiNx, and can make the main grid paste have high opening voltage characteristics; the auxiliary glass powder is a Bi-Si-Mn-Cu oxide system, which has the characteristics of good wettability to silver aluminum paste, and can make the main grid paste have high adhesion and high aging adhesion characteristics and low overlap resistance.

[0017] The organic carrier comprises an organic resin and an organic solvent, wherein the content of the resin is 5.0-25 wt % and the content of the solvent is 75-95 wt %.

[0018] The organic resin includes one or more of ethyl cellulose resin, cellulose acetate butyrate resin, rosin resin, acrylic resin, and polyvinyl butyral.

[0019] Preferably, the organic resin is a mixture of the above resins.

[0020] Resin mixtures can not only broaden the types of resin raw materials, but also combine the advantages of each resin to improve the loading effect of silver powder.

[0021] Further preferably, the content of the organic resin in the organic carrier is: 2.5-10wt% of ethyl cellulose resin, 0.5-5wt% of cellulose acetate butyrate resin, 1.0-5.0wt% of rosin resin, 0.5-5wt% of acrylic resin, and 0.5-10wt% of polyvinyl butyral.

[0022] The organic solvent used in the organic carrier is one or more of the following: butyl carbitol, butyl carbitol acetate, diethylene glycol dibutyl ether, tripropylene glycol monomethyl ether, triethylene glycol butyl ether, alcohol ester dodecahydrate, alcohol ester hexadecene, and acetyl tributyl citrate.

[0023] Preferably, the organic carrier of the present invention is a combination of alcohol, ester and ether organic solvents.

[0024] Further preferably, the content of the organic solvent in the organic carrier is: butyl carbitol 0-10wt%, butyl carbitol acetate 20-40wt%, diethylene glycol dibutyl ether 10-30wt%, tripropylene glycol monomethyl ether 5-20wt%, triethylene glycol butyl ether 0-10wt%, alcohol fat dodeca 0-10wt%, alcohol fat hexadecane 0-10wt%, and acetyl tributyl citrate 0-5wt%.

[0025] The combination of the above-mentioned alcohol, ester and ether organic solvents can improve the compatibility with the resin, thereby improving the uniformity and stability of the organic carrier; the mixed solvent can also evaporate stably and evenly during the silver paste drying process, preventing the volatilization from being too fast or too slow, and reducing the pores generated after the silver paste is dried.

[0026] The organic additives include one or more of thixotropic agents, dispersants, emulsifiers, defoamers, and leveling agents, and preferably contain 0.5-3wt% of thixotropic agent, 0.2-2 wt% of dispersant, 0-0.5wt% of emulsifier, 0-0.5wt% of defoamer, and 0-0.5wt% of leveling agent in the silver paste.

[0027] The present invention provides a method for preparing a main grid silver paste for a TOPCon battery, comprising the following steps:

[0028] (1) Preparation of mixed silver powder: 1-95 wt% of spherical silver powder A, 1-95 wt% of quasi-spherical silver powder B, and 0-10 wt% of nano silver powder C are weighed and mixed according to mass percentage;

[0029] Preferably, the content of nano silver powder C is 2-8wt%.

[0030] (2) Preparation of glass powder: The raw materials of the main glass material and the auxiliary glass material are mixed uniformly and melted at 1300-1600°C for 30-60 minutes; then the glass material is cooled and rolled into sheets, and the rolled glass material is crushed. The crushed glass material is treated by air flow crushing, and the particle size is less than or equal to 4 μm;

[0031] (3) Preparation of organic carrier: weigh 75-95wt% of solvent and 5-25wt% of organic resin by mass percentage, heat to 70-100°C while stirring, continue stirring for 30-60 minutes after the resin is completely dissolved, and then cool to room temperature;

[0032] (4) Preparation of silver paste: 78-85wt% of mixed silver powder, 1-5wt% of main glass powder, 0.1-2wt% of auxiliary glass powder, 8-20wt% of organic carrier, and 0.5-5wt% of organic additive are mixed evenly, and then the mixed silver powder is added and stirred thoroughly. The mixed silver paste is placed on a three-roll mill for dispersion and grinding to obtain the main grid silver paste.

[0033] The main grid silver paste prepared by the present invention has a fineness of less than 8 μm and a viscosity of 90-150 Pa·S / 25° C. at a rotation speed of 5 rpm.

[0034] Beneficial effects of the present invention:

[0035] The main glass powder for the silver paste of the main grid electrode of the TOPCon battery of the present invention is a Pb-Si-Ti-Zn oxide system, which has the characteristic of weak corrosion to SiNx, and can make the main grid paste have a high opening voltage characteristic; the auxiliary glass powder is a Bi-Si-Mn-Cu oxide system, which has the characteristic of good wettability to silver aluminum paste, and can make the main grid paste have high adhesion and high aging adhesion characteristics and low lap resistance. After the main glass powder and the auxiliary glass powder are matched, they are not sensitive to the change of sintering temperature, so that the main grid silver paste has a wide sintering window, which can meet the use of the main grid electrodes of the front and back of the TOPCon battery at the same time.

[0036] The invention adopts a mixed silver powder process to provide a silver paste after sintering the mixed silver powder, which has good density, less damage to the battery PN junction and high photoelectric conversion efficiency.

[0037] The present invention selects suitable organic solvents and resins for combination, so that the organic carrier and the mixed silver powder are assembled more uniformly and have better stability. DETAILED DESCRIPTION

[0038] The present application is further described in detail below in conjunction with the implementation modes. It is to be understood that the specific implementation modes described herein are only used to explain the relevant contents, and are not intended to limit the present application.

[0039] Example 1

[0040] A TOPCon battery main grid electrode silver paste has the following composition by mass percentage: 83.5% mixed silver powder, 1.5% main glass powder, 0.4% auxiliary glass powder, 12.4% organic carrier, 1.5% thixotropic agent, 0.4% dispersant, 0.1% emulsifier, 0.1% defoamer, and 0.1% leveling agent.

[0041] The preparation method is as follows:

[0042] (1) Preparation of mixed silver powder: 92% spherical silver powder A, 5% quasi-spherical silver powder B, and 3% nano silver powder C are weighed and mixed according to mass percentage; the median particle size of the spherical silver powder A is 1.25 μm, and the tap density is 5.6 g / cm 3 The median particle size of the spherical silver powder B is 1.78 μm, and the tap density is 5.8 g / cm 3 The median particle size of the nano silver powder C is 0.8 μm, and the tap density is 4.6 g / cm3; the density of the mixed silver powder after sintering is 7.8 g / cm 3 ;

[0043] (2) The main glass powder has the following components calculated by mole percentage: PbO 24mol%, SiO2 42mol%, TiO2 16mol%, ZnO 8mol%, TeO2 4mol%, Bi2O3 3mol%, MoO3 3mol%; the auxiliary glass powder has the following components calculated by mole percentage: Bi2O3 20mol%, SiO2 45mol%, CuO 16mol%, MnO2 9mol%, TeO2 5mol%, ZnO 3mol%, B2O3 2mol%; the components of the main glass powder and the auxiliary glass powder are mixed evenly in a mixer, and then heated to 1500°C in a high-temperature furnace, kept warm and melted for 60 minutes, and then cooled and rolled into sheets, and the rolled glass material is crushed, and the crushed glass material is polished, ground and graded by a jet mill to obtain the required main glass powder and auxiliary glass powder;

[0044] (3) Preparation of an organic vehicle: 10% butyl carbitol, 35% butyl carbitol acetate, 15% diethylene glycol dibutyl ether, 15% tripropylene glycol monomethyl ether, 5% alcohol lipid dodecahydrate, and 2% acetyl tributyl citrate were weighed and mixed evenly; 7.5% ethyl cellulose resin, 2.5% cellulose acetate butyrate resin, 2.5% rosin resin, 1.5% acrylic resin, and 4% polyvinyl butyral were weighed and added to the mixed solvent, and then heated to 80° C. while stirring. After the resin was completely dissolved, stirring was continued for 60 minutes, and then cooled to room temperature to obtain an organic vehicle;

[0045] (4) Preparation of silver paste: 1.5% of main glass powder, 0.4% of auxiliary glass powder, 12.4% of organic carrier, 1.5% of thixotropic agent, 0.4% of dispersant, 0.1% of emulsifier, 0.1% of defoaming agent and 0.1% of leveling agent are mixed uniformly by mass percentage, and then 83.5% of mixed silver powder is added and stirred thoroughly. The mixed silver paste is placed on a three-roll mill for dispersion and grinding for 6 times. The fineness of the obtained main grid silver paste is less than 8 μm, and the viscosity at a rotation speed of 5 rpm is 108 Pa·S / 25°C.

[0046] Example 2

[0047] The mass percentage composition of the main grid silver paste of this embodiment is as follows: 82% mixed silver powder, 1.5% main glass powder, 0.4% auxiliary glass powder, 14% organic carrier, 1.4% thixotropic agent, 0.4% dispersant, 0.1% emulsifier, 0.1% defoaming agent, and 0.1% leveling agent.

[0048] The preparation method is as follows:

[0049] (1) Preparation of mixed silver powder: 8% spherical silver powder A, 90% quasi-spherical silver powder B, and 2% nano silver powder C are weighed and mixed according to mass percentage; the median particle size of the spherical silver powder A is 1.1 μm, and the tap density is 5.8 g / cm 3 The median particle size of the spherical silver powder B is 1.5 μm, and the tap density is 6.1 g / cm 3 The nano silver powder C has a median particle size of 0.75 μm and a tap density of 4.8 g / cm 3 ; The density of the mixed silver powder after sintering is 8.0g / cm 3 ;

[0050] (2) The components and preparation of the main glass powder and the auxiliary glass powder are the same as those in Example 1;

[0051] (3) The composition and preparation of the organic carrier are the same as those in Example 1;

[0052] (4) Preparation of silver paste: 1.5% of main glass powder, 0.4% of auxiliary glass powder, 14% of organic carrier, 1.4% of thixotropic agent, 0.4% of dispersant, 0.1% of emulsifier, 0.1% of defoaming agent and 0.1% of leveling agent were mixed uniformly according to mass percentage, and then 82% of mixed silver powder was added and stirred thoroughly. The mixed silver paste was placed on a three-roll mill for dispersion and grinding for 6 times. The fineness of the main grid silver paste was less than 8 μm, and the viscosity was 100 Pa·S / 25°C at a rotation speed of 5 rpm.

[0053] Example 3

[0054] The mass percentage composition of the main grid silver paste of this embodiment is as follows: 83.5% mixed silver powder, 1.8% main glass powder, 0.5% auxiliary glass powder, 11.8% organic carrier, 1.7% thixotropic agent, 0.4% dispersant, 0.1% emulsifier, 0.1% defoaming agent, and 0.1% leveling agent.

[0055] The preparation method is as follows:

[0056] (1) The preparation of the mixed silver powder is the same as that in Example 1;

[0057] (2) The main glass powder has the following components calculated by mole percentage: PbO 28mol%, SiO2 36mol%, TiO2 20mol%, ZnO 7mol%, TeO2 5mol%, Bi2O3 4mol%; the auxiliary glass powder has the following components calculated by mole percentage: Bi2O3 19mol%, SiO2 52mol%, CuO 14mol%, MnO2 6mol%, TeO2 4mol%, ZnO 3mol%, MoO3 2mol%; the components of the main glass powder and the auxiliary glass powder are mixed evenly in a mixer, and then heated to 1600°C in a high-temperature furnace, kept warm and melted for 60 minutes, and then cooled and rolled into sheets, and the rolled glass material is crushed. The crushed glass material is polished, ground and graded by a jet mill to obtain the required main glass powder and auxiliary glass powder;

[0058] (3) The composition and preparation of the organic carrier are the same as those in Example 1;

[0059] (4) Preparation of silver paste: 1.8% of main glass powder, 0.5% of auxiliary glass powder, 11.8% of organic vehicle, 1.7% of thixotropic agent, 0.4% of dispersant, 0.1% of emulsifier, 0.1% of defoamer and 0.1% of leveling agent were mixed uniformly by mass percentage, and then 83.5% of mixed silver powder was added and stirred thoroughly. The mixed silver paste was placed on a three-roll mill for dispersion and grinding for 6 times. The fineness of the obtained main grid silver paste was less than 8 μm, and the viscosity at a rotation speed of 5 rpm was 115 Pa·S / 25°C.

[0060] Example 4

[0061] The mass percentage composition of the main grid silver paste of this embodiment is as follows: 83.5% mixed silver powder, 1.5% main glass powder, 0.4% auxiliary glass powder, 10.9% organic vehicle, 2.75% thixotropic agent, 0.5% dispersant, 0.2% emulsifier, 0.15% defoaming agent, and 0.1% leveling agent.

[0062] The preparation method is as follows:

[0063] (1) The preparation of the mixed silver powder is the same as that in Example 1;

[0064] (2) The components and preparation of the main glass powder and the auxiliary glass powder are the same as those in Example 1;

[0065] (3) Preparation of an organic vehicle: 8% of butyl carbitol, 35% of butyl carbitol acetate, 13% of diethylene glycol dibutyl ether, 20% of tripropylene glycol monomethyl ether, 4% of alcohol lipid dodecahydrate, and 2% of acetyl tributyl citrate were weighed and mixed evenly; 8.5% of ethyl cellulose resin, 2.0% of cellulose acetate butyrate resin, 2.0% of rosin resin, 2.5% of acrylic resin, and 3% of polyvinyl butyral were weighed and added to the mixed solvent, and then heated to 80° C. while stirring. After the resin was completely dissolved, stirring was continued for 60 minutes, and then cooled to room temperature to obtain an organic vehicle;

[0066] (4) Preparation of silver paste: 1.5% of main glass powder, 0.4% of auxiliary glass powder, 10.9% of organic carrier, 2.75% of thixotropic agent, 0.5% of dispersant, 0.2% of emulsifier, 0.15% of defoaming agent, and 0.1% of leveling agent are mixed uniformly by mass percentage, and then 83.5% of mixed silver powder is added and stirred thoroughly. The mixed silver paste is placed on a three-roll mill for dispersion and grinding for 6 times. The obtained main grid silver paste has a fineness of less than 8 μm and a viscosity of 112 Pa·S / 25°C at a rotation speed of 5 rpm.

[0067] Example 5

[0068] The mass percentage composition of the main grid silver paste of this embodiment is as follows: 79% mixed silver powder, 1.4% main glass powder, 0.6% auxiliary glass powder, 17.5% organic carrier, 1.0% thixotropic agent, 0.3% dispersant, 0.1% emulsifier, 0.05% defoaming agent, and 0.05% leveling agent.

[0069] The preparation method is as follows:

[0070] (1) Preparation of mixed silver powder: 49% spherical silver powder A, 45% quasi-spherical silver powder B, and 6% nano silver powder C are weighed and mixed according to mass percentage; the median particle size of the spherical silver powder A is 1.2 μm, and the tap density is 5.75 g / cm 3 The median particle size of the spherical silver powder B is 1.8 μm, and the tap density is 5.6 g / cm 3 The nano silver powder C has a median particle size of 0.8 μm and a tap density of 4.6 g / cm 3 ; The density of the mixed silver powder after sintering is 8.5g / cm 3 ;

[0071] (2) The main glass powder has the following components calculated by mole percentage: PbO 12mol%, SiO2 54mol%, TiO2 16mol%, ZnO 13mol%, TeO2 5mol%; the auxiliary glass powder has the following components calculated by mole percentage: Bi2O3 24mol%, SiO2 32mol%, CuO 22mol%, MnO2 14mol%, TeO2 5mol%, ZnO 3mol%; the components of the main glass powder and the auxiliary glass powder are mixed evenly in a mixer, heated to 1450°C in a high-temperature furnace, melted for 60 minutes, cooled and rolled, the rolled glass material is crushed, and the crushed glass material is polished, ground and graded by a jet mill to obtain the required main glass powder and auxiliary glass powder;

[0072] (3) Preparation of an organic vehicle: 8% of butyl carbitol, 32% of butyl carbitol acetate, 12% of diethylene glycol dibutyl ether, 18% of tripropylene glycol monomethyl ether, 4% of alcohol lipid dodecahydrate, and 1% of acetyl tributyl citrate were weighed and mixed evenly; 10.2% of ethyl cellulose resin, 2.8% of cellulose acetate butyrate resin, 2% of rosin resin, 2.5% of acrylic resin, and 7.5% of polyvinyl butyral were weighed and added to the mixed solvent, and then heated to 80° C. while stirring. After the resin was completely dissolved, stirring was continued for 60 minutes, and then cooled to room temperature to obtain an organic vehicle;

[0073] (4) Preparation of silver paste: 1.4% of main glass powder, 0.6% of auxiliary glass powder, 17.5% of organic carrier, 1.0% of thixotropic agent, 0.3% of dispersant, 0.1% of emulsifier, 0.05% of defoaming agent, and 0.05% of leveling agent are mixed uniformly according to mass percentage, and then 79% of mixed silver powder is added and stirred thoroughly. The mixed silver paste is placed on a three-roll mill for dispersion and grinding for 6 times. The fineness of the obtained main grid silver paste is less than 8 μm, and the viscosity at a rotation speed of 5 rpm is 120 Pa·S / 25°C.

[0074] Example 6

[0075] The other steps are the same as those in Example 1, except that step (1) uses a single spherical silver powder A, the median particle size of which is 1.25 μm and the tap density is 5.6 g / cm 3 .

[0076] Example 7

[0077] The other steps are the same as those in Example 1, except that in step (3), a single ethyl cellulose resin is used as the organic resin and added to the mixed solvent.

[0078] Example 8

[0079] The other steps are the same as those in Example 1, except that in step (3), butyl carbitol acetate is used as the organic solvent, and the mixed resin is added to the organic solvent.

[0080] Comparative Example 1

[0081] The main grid silver paste is purchased from outside, and the glass powder used is Pb-Si-Ti-Zn-Bi series.

[0082] Comparative Example 2

[0083] The other steps are the same as those in Example 1, except that in step (2), only main glass powder is added, and the components calculated by molar percentage are as follows: PbO 24mol%, SiO242mol%, TiO2 16mol%, ZnO8mol%, TeO2 4mol%, Bi2O33mol%, MoO3 3mol%; the glass powder is added into a high-temperature furnace and heated to 1500°C, kept warm and melted for 60 minutes, then cooled and rolled into sheets, and the rolled glass material is crushed. The crushed glass material is polished, ground and graded by a jet mill to obtain the desired glass powder.

[0084] Detection method:

[0085] 1. Slurry viscosity:

[0086] The test was carried out using a rotational viscometer (52 rotor viscometer) at room temperature 25°C.

[0087] 2. Preparation of single crystal cells:

[0088] Using TOPCon silicon wafers with consistent square resistance, the prepared main grid silver paste and the same fine grid silver paste are printed on the front and back main grids and front and back fine grids of the battery respectively by screen printing process, and then dried - sintered - cooled to room temperature to obtain TOPCon battery cells.

[0089] 3.IV electrical performance test:

[0090] Use IV tester to perform IV electrical performance test on TOPCon cells.

[0091] 4. Welding tension:

[0092] The main grid electrode on the front side of the battery was welded at 340°C using a 0.35 mm tin-coated solder strip, and a tensile tester was used to perform a tensile test. The test results are shown in Table 1.

[0093] Table 1

[0094]

[0095]

[0096] From the above results, it can be seen that the main glass powder and the auxiliary glass powder are used in combination in Examples 1, 3 and 4, and the opening voltage and welding tensile force of the TOPCon battery printed with the main grid silver paste are higher than those of the comparison paste (Comparative Examples 1 and 2).

[0097] In Examples 2 and 5, the mixed silver powder content was adjusted to reduce the cost, but the photoelectric conversion efficiency and welding tensile force of the prepared TOPCon battery printed with low-silver-containing main grid silver paste were similar to or slightly higher than those of Comparative Example 1.

[0098] The single silver powder, single resin and single solvent used in Examples 6, 7 and 8 mainly affect the current of the battery after printing of the silver paste. The current is lower than that of Example 1, but the overall battery efficiency and tension are higher than those of Comparative Examples 1 and 2.

[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A TOPCon battery main grid silver paste, characterized in that: include: 78-85wt% of mixed silver powder, 1-5wt% of main glass powder Pb-Si-Ti-Zn oxide, 0.1-2wt% of auxiliary glass powder Bi-Si-Mn-Cu oxide, 8-20wt% of organic carrier, and 0.5-5wt% of organic additive; The mixed silver powder is a mixture of spherical silver powder A, quasi-spherical silver powder B and nano silver powder C; The fineness of the main grid silver paste is less than 8 μm, and the viscosity is 90-150 Pa·S. The test conditions of the viscosity are: temperature 25° C., rotation speed 5 rpm; The main glass powder includes the following components calculated by molar percentage: PbO 8-28mol%, SiO2 25-50mol%, TiO2 5-25mol%, ZnO 4-16mol% and X 1-10mol%, wherein X includes any one or a combination of two or more of TeO2, Bi2O3, B2O3, MgO, CaO, BaO, Cr2O3, MoO3 and WO3; The auxiliary glass powder includes the following components calculated in molar percentage: Bi2O3 5-24mol%, SiO2 30-55mol%, CuO 5-25mol%, MnO2 1-15mol% and Y 1-10mol%, wherein Y includes any one or a combination of two or more of TeO2, ZnO, B2O3, MgO, CaO, BaO, Cr2O3, MoO3 and WO3.

2. The main grid silver paste according to claim 1, characterized in that: The median particle size of the spherical silver powder A is 1.1-1.4 μm, and the tap density is 5-6 g / cm 3 The median particle size of the spherical silver powder B is 1.5-2.0 μm, and the tap density is 5.5-6.5 g / cm 3 The nano silver powder C has a median particle size of 0.5-0.8 μm and a tap density of 4.5-5.5 g / cm3.

3. The main grid silver paste according to claim 1 or 2, characterized in that: The content of spherical silver powder A is 1-95wt%, the content of quasi-spherical silver powder B is 1-95wt%, and the content of nano silver powder C is 0-10wt%; the sintered density of the mixed silver powder is 6.5-9.5 g / cm 3 .

4. The main grid silver paste according to claim 3, characterized in that: The content of the nano silver powder C is 2-6wt%.

5. The main grid silver paste according to claim 1, characterized in that: The organic carrier includes an organic resin and an organic solvent, wherein the resin content is 5.0-25 wt % and the solvent content is 75-95 wt %; the organic resin includes one or more of ethyl cellulose resin, cellulose acetate butyrate resin, rosin resin, acrylic resin, and polyvinyl butyral ester; The organic solvent used in the organic carrier is one or more of the following: butyl carbitol, butyl carbitol acetate, diethylene glycol dibutyl ether, tripropylene glycol monomethyl ether, triethylene glycol butyl ether, alcohol ester dodecahydrate, alcohol ester hexadecene, and acetyl tributyl citrate.

6. The main grid silver paste according to claim 5, characterized in that: The content of the organic resin in the organic carrier is: 2.5-10 wt % of ethyl cellulose resin, 0.5-5 wt % of cellulose acetate butyrate resin, 1.0-5.0 wt % of rosin resin, 0.5-5 wt % of acrylic resin, and 0.5-10 wt % of polyvinyl butyral. The content of the organic solvent in the organic carrier is: 0-10 wt% of butyl carbitol, 20-40 wt% of butyl carbitol acetate, 10-30 wt% of diethylene glycol dibutyl ether, 5-20 wt% of tripropylene glycol monomethyl ether, 0-10 wt% of triethylene glycol butyl ether, 0-10 wt% of alcohol fat 12, 0-10 wt% of alcohol fat 16, and 0-5 wt% of acetyl tributyl citrate.

7. The method for preparing the TOPCon battery main grid silver paste according to any one of claims 1 to 6, comprising the following steps: (1) Preparation of mixed silver powder: weigh spherical silver powder A, quasi-spherical silver powder B, and nano silver powder C and mix them; (2) Preparation of glass powder: The raw materials of the main glass material and the auxiliary glass material are mixed evenly and melted; then the glass material is cooled and rolled into sheets, and the rolled glass material is crushed. The crushed glass material is treated by air flow crushing; (3) Preparation of organic carrier: weigh organic solvent and organic resin, heat with stirring until the organic resin is completely dissolved, continue stirring, and then cool to room temperature; (4) Preparation of silver paste: Weigh mixed silver powder, main glass powder, auxiliary glass powder, organic carrier, and organic additive, first mix the glass powder, organic carrier and organic additive evenly, then add the mixed silver powder and stir evenly, disperse and grind the mixed silver paste to obtain the main grid silver paste.

8. The preparation method according to claim 7, characterized in that: The melting conditions of step (2) are: melting at 1300-1600° C. for 30-60 min; the particle size after air flow crushing is less than or equal to 4 μm; and step (3) heating to 70-100° C. and continuing stirring for 30-60 minutes.

9. The battery busbar silver paste according to any one of claims 1 to 6 or the busbar silver paste obtained by the preparation method according to claim 7 or 8 is applied to TOPCon batteries.

Citation Information

Patent Citations

  • All-aluminum back-field back silver paste, preparation method thereof, and application thereof

    CN109524150A